IMPLEMENTASI KONSEP PENDIDIKAN ISLAM PERSPEKTIF IBNU TAIMIYAH DAN MUHAMMAD ABDUH DALAM RPP KURIKULUM 2013 - Drestiani, Tri Anti; Fahmi, Ari Khairurrijal (Universitas Muhammadiyah Prof Dr Hamka, 2018)
Islamic education is a concept of human education based on Islam. Various thought efforts in order to realize education according to Al-Qur’an and Sunnah such as the thoughts of Ibn Taymiyyah and Muhammad Abduh. The author analyzed their thoughts of education and its implementation in Indonesia now. The system, objectives, curriculum, methods and content of Islamic education materials can be innovated in a sustainable periods. This thesis is using a qualitative research. The authors collect data by using library research with content analysis techniques. The author tries to implement the incorporation of the Islamic education system from the two figures through an analysis that made into RPP according to the 2013 Curriculum. How to implement it by using the imtaq method. Imtaq method is a method of learning that is modified by researchers based on the Qur’an and Hadith on structural material. This is expected to improve the quality of students, both IQ, EQ and SQ. Keywords: Islamic Education, Ibn Taymiyyah, Muhammad Abduh, 2013 Curriculum RPP, Imtaq.